Tocilizumab-associated multifocal cerebral thrombotic microangiopathy - Jewell, P; Ansorge, O; Kuker, W; Irani, S; Zamboni, G (American Academy of Neurology, 2016)
Tocilizumab is a humanized monoclonal antibody that targets the interleukin-6 receptor (IL-6-R). It is approved for use in moderate to severe refractory rheumatoid arthritis and more recently has been found to be effective in treating neuromyelitis optica.1 Common side effects include raised hepatic transaminases, gastroenteritis, infections, and hypertension. Neurologic side effects have been described in 2 single case reports, which were confounded by the concomitant use of other antirheumatic therapies and lengthy durations between tocilizumab administration and onset of neurologic symptoms.2,3 We describe the clinico-histologic analysis of an acute neurologic deterioration 2 weeks after the first infusion of tocilizumab.